Meis homeobox genes control progenitor competence in the retina - Dupacova, Naoko; Antosova, Barbora; Paces, Jan; Kozmik, Zbynek (Proceedings of the National Academy of Sciences of the United States of America, 2021)
The vertebrate eye is derived from the neuroepithelium, surface ectoderm, and extracellular mesenchyme. The neuroepithelium forms an optic cup in which the spatial separation of three domains is established, namely, the region of multipotent retinal progenitor cells (RPCs), the ciliary margin zone (CMZ)-which possesses both a neurogenic and nonneurogenic potential-and the optic disk (OD), the interface between the optic stalk and the neuroretina. Here, we show by genetic ablation in the developing optic cup that Meis1 and Meis2 homeobox genes function redundantly to maintain the retinal progenitor pool while they simultaneously suppress the expression of genes characteristic of CMZ and OD fates. Furthermore, we demonstrate that Meis transcription factors bind regulatory regions of RPC-, CMZ-, and OD-specific genes, thus providing a mechanistic insight into the Meis-dependent gene regulatory network. Our work uncovers the essential role of Meis1 and Meis2 as regulators of cell fate competence, which organize spatial territories in the vertebrate eye.
Keywords: Cell Differentiation; Homeodomain Proteins; vývojová regulace genové exprese; Transcription Factors; retina; Gene Knockdown Techniques; Gene Expression Regulation, Developmental; transkripční faktory; Retina; obratlovci; zvířata; Vertebrates; development; genový knockdown; Stem Cells; buněčná diferenciace; kmenové buňky; homeodoménové proteiny; Meis; Animals